Investment, resolution of risk, and the role of affect - Frans van Winden; Michal Krawczyk; Astrid Hopfensitz (Center for Economic Studies and ifo Institute (CESifo), 2010)
This experimental study is concerned with the impact of the timing of the resolution of risk on people's willingness to take risks, with a special focus on the role of affect. While the importance of anticipatory emotions has so far been only inferred from decisions regarding hypothetical choice problems, we had participants put their own money at risk in a real investment task. Moreover, emotions were explicitly measured, including anticipatory emotions experienced during the waiting period under delayed resolution (which involved two days). Affective traits and risk attitudes were measured through a web-based questionnaire before the experiment and participants' preferences for resolution timing, risk, and time were incentive compatibly measured during the experiment. Main findings are that delayed resolution can affect investment, that the effect depends on the risk involved, and that (among all the measures considered) only emotions can explain our results, albeit in ways that are not captured by existing models.
Keywords: C91; D81; G11; 330; investment decision; delayed resolution of risk; emotions; experiment; Investition; Entscheidung bei Risiko; Emotion; Test